An NMR-based approach reveals the core structure of the functional domain of SINEUP lncRNAs. Issue 16 (22nd July 2020) - Ohyama, Takako; Takahashi, Hazuki; Sharma, Harshita; Yamazaki, Toshio; Gustincich, Stefano; Ishii, Yoshitaka; Carninci, Piero
Abstract: Long non-coding RNAs (lncRNAs) are attracting widespread attention for their emerging regulatory, transcriptional, epigenetic, structural and various other functions. Comprehensive transcriptome analysis has revealed that retrotransposon elements (REs) are transcribed and enriched in lncRNA sequences. However, the functions of lncRNAs and the molecular roles of the embedded REs are largely unknown. The secondary and tertiary structures of lncRNAs and their embedded REs are likely to have essential functional roles, but experimental determination and reliable computational prediction of large RNA structures have been extremely challenging. We report here the nuclear magnetic resonance (NMR)-based secondary structure determination of the 167-nt inverted short interspersed nuclear element (SINE) B2, which is embedded in antisense Uchl1 lncRNA and upregulates the translation of sense Uchl1 mRNAs. By using NMR 'fingerprints' as a sensitive probe in the domain survey, we successfully divided the full-length inverted SINE B2 into minimal units made of two discrete structured domains and one dynamic domain without altering their original structures after careful boundary adjustments. This approach allowed us to identify a structured domain in nucleotides 31–119 of the inverted SINE B2. This approach will be applicable to determining the structures of other regulatory lncRNAs.